Analisis Implementasi Cash Waqf Linked Sukuk (CWLS) Perspektif Prinsip Ekonomi Syariah - Riska Delta Rahayu; Moh. Andre Agustianto (Management of Zakat and Waqf Journal (MAZAWA), 2020)
Waqf played two important roles in Islamic history, namely in economic as well as social. An innovation in developing waqf is the Cash Waqf Linked Sukuk (CWLS) which is an integration between the waqf funds invested through State Sharia Securities (SBSN) or Sukuk. This study aims to examine the role of CWLS in the economy and society based on an Islamic economic perspective. This research is a type of library research (literature study) with a qualitative approach. The implementation of Cash Waqf Linked Sukuk management has been carried out in accordance with an Islamic economic perspective which is based on sharia principles and has been determined in accordance with the DSN-MUI Fatwa on Sukuk Waqf. The results of the study reveal that the implementation of CWLS has also met the required pillars and in managing the waqf funds it is allocated for halal activities and according to sharia principles. Cash Waqf Linked Sukuk has the potential for economic and social development in society because it aims to achieve the benefit and welfare of the community in general